Implementation of the FIFA 11+ football warm up program: How to approach and convince the Football associations to invest in prevention - Bizzini, M.; Junge, A.; Dvorak, J. (British Journal of Sports Medicine, 2013)
In the last decade, injury prevention has received a lot of attention in sports medicine, and recently international sports-governing bodies, such as the International Olympic Committee, declared the protection of the athletes` health as one of their major objectives.In 1994, the Fédération Internationale de Football Association (FIFA) established its Medical Assessment and Research Centre (F-MARC) with the aim `to prevent football injuries and to promote football as a health-enhancing leisure activity, improving social behaviour`. Since then, FIFA has developed and evaluated its injury-prevention programmes `The 11` and `FIFA 11+` have demonstrated in several scientific studies how simple exercise-based programmes can decrease the incidence of injuries in amateur football players. This paper summarises 18 years of scientific and on-field work in injury prevention by an international sports federation (FIFA), from formulating the aim to make its sport safer to the worldwide dissemination of its injury-prevention programme in amateur football.